(untitled) - Ehrlich, Paul R. (Washington, 1996)
This book mentions the global's warming fiction. Ozone depletion should be of no concern and that the earth can support many times its current population. Chapters cover population growth, food supply, natural resources, species diversity, toxic substances, global warming and economics.
Keywords: Anti-environmentalism,Environmental degradation